Urbanization Analysis of Land Surface Temperature Modeling in the Peri-Urban of Surakarta - Rita Noviani; Istiyanti Nur Marfuah; Aditya Eka Saputra (Universitas Negeri Medan, 2024)
The rapid development of urban areas characterized by urbanization has caused various impacts, such as LST. The Peri-Urban area of Surakarta City is one of the areas that experiences similar conditions. This study aims to measure urbanization through the urban form, population, and land urbanization and modeling urbanization of Land Surface Temperature. The method used in this study is modeling using Ordinary least squares (OLS) and Geographically Weighted Regression (GWR). Data processing tools to support this research are ArcGIS and Google Earth Engine. The combination of ArcGIS and Google Earth Engine makes LST modeling more accurate. The measurement results show that the urbanization rate in the peri-urban area of Surakarta City, based on the parameters of land urbanization and urban form, tends to move to the South and West sides with a higher population in areas close to Surakarta City. The results of this study show that GWR modeling is better at explaining the relationship of urbanization with LST than OLS models based on AICc numbers. The relationship of urbanization with population parameters, population density, percentage of built-up land, and urban form with LST using the GWR model of 66.17% and the OLS model reveals that urbanization.Keywords: GWR; LST; OLS; Urbanization; Urban form